Surface guided radiation therapy: An international survey on current clinical practice. (June 2022) - Batista, V.; Gober, M.; Moura, F.; Webster, A.; Oellers, M.; Ramtohul, M.; Kügele, M.; Freislederer, P.; Buschmann, M.; Anastasi, G.; Steiner, E.; Al-Hallaq, H.; et al.
Highlights: First survey of SGRT clinical practice in Europe and beyond. Wide application range (sites and techniques) with diverse clinical use. Strong reliance on vendors for methods, training and quality assurance. Hurdles include cost, integration issues and lack of demonstrated clinical value. Despite some weaknesses a majority believe that SGRT will become standard of care. Abstract: Introduction: Surface Guided Radiation Therapy (SGRT) is being increasingly implemented into clinical practice across a number of techniques and irradiation-sites. This technology, which is provided by different vendors, can be used with most simulation- and delivery-systems. However, limited guidelines and the complexity of clinical settings have led to diverse patterns of operation. With the aim to understand current clinical practice a survey was designed focusing on specifics of the clinical implementation and usage. Materials and methods: A 32-question survey covered: type and number of systems, quality assurance (QA), clinical workflows, and identification of strengths/limitations. Respondents from different professional groups and countries were invited to participate. The survey was distributed internationally via ESTRO-membership, social media and vendors. Results: Of the 278 institutions responding, 172 had at least one SGRT-system and 136 use SGRT clinically. Implementation and QA were primarily based on the vendors' recommendations and phantoms. SGRT was mainly implemented in breast RT (116/136), with strong but diverse representation of other sites. Many (58/135) reported at least partial elimination of skin-marks and a third (43/126) used open-masks. The most common imaging protocol reported included the combination of radiographic imaging with SGRT. Patient positioning (115/136), motion management (104/136) and DIBH (99/136) were the main applications. Main barriers to broader application were cost, system integration issues and lack of demonstrated clinical value. A lack of guidelines in terms of QA of the system was highlighted. Conclusions: This overview of the SGRT status has the potential to support users, vendors and organisations in the development of practices, products and guidelines.